Investigating the Relationship between Employee Empowerment and the Development of an Entrepreneurial Culture at Fatemieh Technical and Vocational University of Bandar Abbas - Aryana, Azade; Siyahouei, Reza Ameri; Mahmoudi, Tahereh (International Review of Management and Marketing, 2017)
This study has been conducted with the aim of investigating the relationship between employee empowerment and the development of an entrepreneurial culture Fatemieh Technical and Vocational University of Bandar Abbas. This is a descriptive and correlational research. The sample size was 113 participants (85 females and 28 males) who were selected via simple random sampling method. The research tool was Spritzer Psychological Empowerment Scale and Entrepreneurial Culture Questionnaire. The data obtained from the study were analyzed using Pearson correlation coefficient. The research findings showed that there is a relationship between employee empowerment and the development of an entrepreneurial culture in Fatemieh Technical and Vocational University of Bandar Abbas, there is a significant relationship between sense of competence (self-efficacy) and the development of an entrepreneurial culture in Fatemieh Technical and Vocational University of Bandar Abbas, there is a significant relationship between the sense of having the right of choice (independence) and the development of an entrepreneurial culture in Fatemieh Technical and Vocational University of Bandar Abbas, there is a significant relationship between sense of meaning and the development of an entrepreneurial culture in Fatemieh Technical and Vocational University of Bandar Abbas, and there is a significant relationship between sense of trust in other employees and the development of an entrepreneurial culture in Fatemieh Technical and Vocational University of Bandar Abbas. Keywords: Empowerment, Development of Entrepreneurial Culture, Employees, Fatemieh Technical and Vocational University JEL Classifications: E37, E32, C53, C5